Perancangan Pusat Budaya Wisata Bukit Sewu Sambang Banyuwangi Berdasarkan Local Wisdom Dengan Pendekatan Sustainable Design (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
The Sewu Sambang Tourism Area is located in Banyuwangi Regency, East Java Province. This area has a unique culture and natural beauty that is very interesting to visit. Therefore, the design of this tourist area was carried out using a sustainable design approach. The design was carried out by considering aspects of ecological, social and economic sustainability. Ecological aspects are taken into account by selecting environmentally friendly building materials, good waste management and the use of renewable energy. Social aspects are taken into account by involving local communities in managing tourist areas and paying attention to local wisdom in design. The economic aspect is considered by building small and medium businesses that support tourist areas, so that they can increase the income of the surrounding community. The design of this tourist area involves sustainable land use, so that it does not damage the surrounding environment. The land used to build tourist attractions such as buildings, parks and parking lots is also adapted to the surrounding environmental conditions, so that it does not disturb the life of local flora and fauna. Apart from that, the use of renewable energy such as solar panels is also carried out to meet electricity needs in tourist areas. The design of this tourist area also pays attention to local wisdom by using building materials and furniture produced by local craftsmen. Apart from that, local wisdom is also demonstrated through art and cultural exhibitions, as well as the use of regional specialties. By designing a sustainable Sewu Sambang tourist area, it is hoped that it can improve the quality of life of the surrounding community, increase community income, and preserve local culture and environment.